The origin and dynamics of solar magnetism - Thompson, M. J. (Space sciences series of ISSI, 2009)
The articles collected in this volume present all aspects of solar magnetism: from its origin in the solar dynamo to its evolution and dynamics that create the variability of solar phenomena, its well-known 11-year activity cycle that leads to the ever-changing pattern of sunspots and active regions on the Sun. Several contributions deal with the solar dynamo, the driver of many solar phenomena. Other contributions treat the transport and emergence of the magnetic flux through the outer layers of the Sun. The coupling of magnetic fields from the surface to the solar corona and beyond is also described, together with current studies on the predictability of solar activity. This book is aimed at researchers and graduate students working in solar physics and space science. It provides a full review of our current understanding of solar magnetism by the foremost experts in the field. Introduction to solar magnetism: the early years - Solar magnetism: the state of our knowledge and ignorance - Chaos and intermittency in the solar cycle - The solar dynamo - Flux-transport solar dynamos - The solar dynamo: the role of penetration, rotation and shear on convective dynamos - Advances in theory and simulations of large-scale dynamos - Planetary dynamos from a solar perspective - Observations of photospheric dynamics and magnetic fields: from large-scale to small-scale flows - Large scale flows in the solar convection zone - Photospheric and subphotospheric dynamics of emerging magnetic flux - The topology and behavior of magnetic fields emerging at the solar photosphere - Sunspots: from small-scale inhomogeneities towards a global theory - Recent evidence for convection in sunspot penumbrae - Helioseismology of sunspots: a case study of NOAA region 9787 - Small-scale solar magnetic fields - Coupling from the photosphere to the chromosphere and the corona - magnetic flux emergence, activity, eruptions and magnetic clouds: following magnetic field from the sun to the heliosphere - Coronal holes and open magnetic flux - Solar cycle forecasting - Coronal magnetism: difficulties and prospects - ISSI workshop on solar magnetism: concluding remarks.